117. Synergistic use in external beams breast irradiation of two in vivo monitoring devices: A study in anthropomorphic female phantom. (December 2018) - Arilli, C.; Wandael, Y.; Casati, M.; Marrazzo, L.; Galeotti, G.; Calus, S.; Grusio, M.; Pallotta, S.; Talamonti, C.
Abstract : Purpose: To evaluate the sensitivity of two systems for in vivo dosimetry, the IQM detector (iRT Systems GmbH, Koblenz, Germany) and the SoftDiso software (Best Medical Srl, Italy), in detecting delivery and set-up errors which can occur in 3DCRT external breast irradiation. Methods: IQM is a transmission chamber mounted below the MLC, whose signal is dependent on radiation fluence [1 ]. SoftDiso reconstructs the dose distribution at the isocenter plan using the information derived from treatment EPID images and calculates the R-value, defined as the ratio between measured and planned dose at the isocenter [2 ]. To simulate the female anatomy, the ALDERSON-RANDO phantom was modified with two silicon breast prosthesis. A 3DCRT plan of left breast was created and modified to mimic output errors (adding 2–3-5–10 MU) and a jaw position error (opening and closing one jaw 2–3-5–7 mm). Additionally set-up errors were simulated by moving the phantom in anterior-posterior direction (2–3-5–10 mm) and by rotating it (1°–2.8°). The deviations of IQM signal and R-value from the original values were evaluated for all plans and phantom positions. Results: The IQM signal and R-value linearly increase with the MU increment (R 2 = 1 and 0.97 respectively) (Fig. 1a). The IQM signal is linearly correlated with the jaws position (R 2 = 0.93 and 0.97 for close and open jaw), while R-value is less sensitive to jaws positioning variations (Fig. 1b, c). R-value linearly increase with the extent of phantom displacement (R 2 = 0.99) but it is not sensitive to phantom rotations (Fig. 1d, e). Conclusions: Both devices are able to detect small output variations. SoftDiso is less sensitive to jaws positioning deviations than IQM. Instead SoftDiso is suitable to detect set-up errors. The synergistic use of both devices is relevant to improve the dosimetric accuracy in breast external irradiation.